-54-4x=23+3x

Simple and best practice solution for -54-4x=23+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -54-4x=23+3x equation:



-54-4x=23+3x
We move all terms to the left:
-54-4x-(23+3x)=0
We add all the numbers together, and all the variables
-4x-(3x+23)-54=0
We get rid of parentheses
-4x-3x-23-54=0
We add all the numbers together, and all the variables
-7x-77=0
We move all terms containing x to the left, all other terms to the right
-7x=77
x=77/-7
x=-11

See similar equations:

| -23+x=-6x+40 | | k2−12k-14=0 | | 6(x-3)=3(x-2) | | x+2x−4+(2x−4)+3=5x | | -3x+6=-7-4x | | 29-5x=-31+x | | 40+6x-2=90 | | x+2x−4+(2x−4)=5x | | -9(x-2)=3(x-2) | | 7(x+2)=2(2x-4 | | 4/10(x-2/1)=13/4*2/10x) | | -2(2x-5)=3(x+6) | | -2(2x-5)=3(x+6 | | 25=3-3s | | x+2x−4+(2x−4)+3=35 | | 6(x-3)=3(x-2 | | 2/5-3y=2y-2/5 | | 3(x-4)^2=27 | | 2(x+30)^2+(-1800)=0 | | 3(3x-4)=-2(x+5) | | 3(3x-4)=-2(x+5 | | 2(x+30)^2+1800=0 | | 1200x=5000+700x | | -5(x-4)=-2(x-3) | | 15-2b=- | | y=-1(0)2y=4 | | -1(0)2y=4 | | 3(x+10)=-21 | | 1/4x+1/8x+1/6x=4.75 | | 10=-b^2+8b-5 | | 3/2=18/x | | 10=-b^2 |

Equations solver categories